TRAIT KEPRIBADIAN DAN KEPERCAYAAN KONSUMEN UNTUK BERBELANJA PADA TOKO ONLINE - Gumgum Gumelar, Intan Pandina (Perspektif Ilmu Pendidikan, 2014)
This study investigated the influence of the interaction between personality traits and consumer trust in online shopping behavior. The study included 120 subjects who ever did shopping in online shop and and lived in Jakarta. The research conducted at july 2013 employed quantitative approach with the regression analysis. The samples were selected using a nonprobability accidental sampling method. The instrument consisted of two scales: consumers trust and scale of big five personality traits. The result showed, there is significant effect between the big five personality traits toward consumers trust for shopping in online shop. Regression equation obtained: Y = 38,315 + 0,044 X1 + 0,076 X2 + 0,406 X3 + 0,269 X4 + 0,067 X5, which means there is a positive effect between the big five personality traits toward consumers trust for shopping in online shop with the value F = 4,618; p = 0,001 < 0.05 (significant). The amount of effect (Adjustment R Square) to the occurrence of the big five personality traits and consumers trust for shopping in online shop is 0,132 meaning the big five personality traits affect the consumers trust for shopping in online shop by 13,2% and the remaining 86,8% affected by another factors, outside of the big five personality traits.